1982
DOI: 10.1093/bja/54.6.623
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Lorazepam and Trimeprazine for Oral Premedication in Paediatric Anaesthesia

Abstract: One hundred and ninety-nine children received lorazepam 0.05 mg kg-1 or trimeprazine 3 mg kg-1 as oral premedication in a double-blind trial. Lorazepam proved more palatable and produced a cheerful demeanour, but possessed no significant advantages on overall assessment before surgery. Following operation, restlessness with vomiting, and evidence of retrograde amnesia occurred more frequently with lorazepam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Anterograde amnesia was evaluated in all studies, whereas retrograde amnesia was assessed in only 10 studies [7,33,35,37,39,40,52,54,60,66]. Amnesia was evaluated mainly by measuring patient recall of pictures/toys and events, except for the six trials [13,41,16,19,38,42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterograde amnesia was evaluated in all studies, whereas retrograde amnesia was assessed in only 10 studies [7,33,35,37,39,40,52,54,60,66]. Amnesia was evaluated mainly by measuring patient recall of pictures/toys and events, except for the six trials [13,41,16,19,38,42].…”
Section: Resultsmentioning
confidence: 99%
“…Benzodiazepines were compared to non-benzodiazepines in 13 studies [18,44,45,48,50,51,5660,70,71]. In four studies, anterograde amnesia was significantly more likely when benzodiazepines were used than when nitrous oxide [50], antihistamines [45,48,60], or triclofos [48] were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the dose causes excessive and prolonged post-operative drowsiness which is not appreciated by many [12]. It is more humane to give sedating dose of ketamine by intramuscular injection than to struggle with a distressed 4 Subanaesthetic Doses of Intramuscular Ketamine and crying child.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lorazepam has generally been reported to provide poor sedation, while its anticonvulsant properties make it a preferred agent for acute seizure disorders in children. [83][84][85][86] Lorazepam has been associated with myoclonus and other adverse effects in low-birthweight infantsJ8?88] Studies have reported an increased frequency of complications and endotracheal intubation in chil- a The lack of recent comprehensive data on morphine and meperidine precludes an accurate assessment of the serious complications associated with their use for conscious sedation in children.…”
Section: Benzodiazepinesmentioning
confidence: 99%